Here is a problem : Prove if gcd (a,b) = e then gcd (a, b/e)= 1 Hint : use the fact that gcd(a,bc)= gcd(a,b) gcd(a,c) Please help me I am lost
Follow Math Help Forum on Facebook and Google+
Originally Posted by tareksha Here is a problem : Prove if gcd (a,b) = e then gcd (a, b/e)= 1 Hint : use the fact that gcd(a,bc)= gcd(a,b) gcd(a,c) Please help me I am lost I have a counterexample: gcd (6, 4) = 2 but gcd (6, 4/2) = gcd (6, 2) = 2 A counterexample for the hint would be: gcd (6, 4) = 2 whereas gcd (6, 2)*gcd (6, 2) = 4
Originally Posted by alexmahone I have a counterexample: gcd (6, 4) = 2 but gcd (6, 4/2) = gcd (6, 2) = 2 A counterexample for the hint would be: gcd (6, 4) = 2 whereas gcd (6, 2)*gcd (6, 2) = 4 Thank you so much brother . I appreciate your response
View Tag Cloud